Magnetic nanoparticle assembly arrays prepared by hierarchical self-assembly on a patterned surface1. Issue 11 (21st March 2015) - Wen, Tianlong; Zhang, Dainan; Wen, Qiye; Zhang, Huaiwu; Liao, Yulong; Li, Qiang; Yang, Qinghui; Bai, Feiming; Zhong, Zhiyong
<x xml:space="preserve">Abstract</x> Inverted pyramid hole arrays were fabricated by photolithography and used as templates to direct the growth of colloidal nanoparticle assemblies.